Probing the system behind variable antigen expression in animal pathogen Trypanosoma congolense - McDonald, Jennifer (2018)
Antigenic variation is a strategy adopted by many pathogens to evade the host immune system. African trypanosomes, in particular Trypanosoma brucei, are models for antigenic variation in parasites. These organisms periodically switch the identity of their major surface protein, variable surface glycoprotein (VSG), and as a result are able to survive extracellularly in the blood of vertebrate hosts for extended periods. In T. brucei, there are over 3000 VSG genes but only 1 is transcribed at a time from a telomeric expression site. Apparently uniquely, RNA Polymerase I (Pol I) transcribes the active expression site and this occurs in an extranucleolar location, known as the expression site body.